Growth hormone associated with treatment efficacy of immune checkpoint inhibitors in gastric cancer patients - Zhao, Yue; Ji, Zhengzheng; Li, Jiasong; Zhang, Shasha; Wu, Chensi; Zhang, Ruixing; Guo, Zhanjun (Frontiers in Oncology, 2022)
Background: Immune checkpoint inhibitors (ICIs) combined with chemotherapy has been widely employed to improve the outcome of gastric cancer patients. In present study, the impact of post-treatment growth hormone (GH) levels on the treatment efficacy of ICIs for advanced gastric cancer (AGC) patients was assessed. Methods: Seventy five AGC patients treated with anti-PD-1 antibodies at The Fourth Hospital of Hebei Medical University were involved. We divided AGC patients into two groups as high GH group and low GH group based on GH level. Immunotherapy efficacy was assessed in terms of objective response rate, disease control rate (DCR), progression-free survival (PFS) and overall survival (OS) based on the National Comprehensive Cancer Network Guidelines. The enumeration data was compared by χ2 test or Fisher's exact test. Survival curves were drawn by the Kaplan-Meier method, and comparisons between the curves were made using the log-rank test. Multivariate survival analysis was performed using a Cox proportional hazards model. Results: The higher GH levels were associated with lower DCR of ICIs with DCR of 30.0% in high GH group and 53.3% in low GH group (P=0.046). The subsequent univariate analysis showed that high GH was associated with both shorter PFS (P=0.016) and shorter OS at the borderline statistical level (P=0.052) in AGC patients treated with ICIs. Cox model analysis also proved that the GH level was an independent risk factor for the outcome of AGC patients (PFS: P=0.013, HR, 2.424, 95%CI, 1.202-4.890; OS: P=0.014, HR, 3.301, 95%CI, 1.279-8.519). Conclusions: The post-treatment GH level might be a predictor for ICIs treatment in AGC patients.